Análise de performance de fundos de investimento com carteiras em ações exclusivos para regimes previdenciários - Costa, Mariana Paulino (2014)
This research addresses the field of Investment Funds with a focus on Funds with equity portfolios, constituted for social security entities, whether public or private, with the objective of evaluating the performance of these funds, through the Sharpe, Sortino and Calmar indices, over the period from 2009 to 2012. The results obtained showed similar rankings for the risk metrics used and the existence of a trend in the performance of the Funds with good results and the Funds with low performance.